The SIRT1 deacetylase protects mice against the symptoms of metabolic syndrome. Issue 3 (2nd December 2013) - Caron, Annabelle Z.; He, Xiaohong; Mottawea, Walid; Seifert, Erin L.; Jardine, Karen; Dewar‐Darch, Danielle; Cron, Greg O.; Harper, Mary‐Ellen; Stintzi, Alain; McBurney, Michael W.
Abstract : Type 2 diabetes, hepatic steatosis, and gut dysbiosis are pathophysiological consequences of obesity. Sirtuin (SIRT)‐1 is a protein deacetylase implicated in the regulation of metabolic activity. We set out to determine whether the catalytic activity of SIRT1 plays a role in the development of metabolic syndrome, hepatic steatosis, and the distribution of gut microbiota. We challenged with a high‐fat diet (HFD) a strain of mice homozygous for a Sirt1 allele carrying a point mutation that ablates the deacetylase activity of SIRT1. When compared to wild‐type animals, mice lacking SIRT1 catalytic activity rapidly accumulated excessive hepatic lipid while fed the HFD, an effect evident within 2 wk of HFD feeding. Both white and brown adipose depots became hypertrophic, and the animals developed insulin resistance. The ratio of the major phyla of gut microbiota (Firmicutes and Bacteroidetes) increased rapidly in the SIRT1‐deficient mice after HFD challenge. We conclude that the deacetylase activity of SIRT1 plays an important role in regulating glucose and hepatic lipid homeostasis. In addition, the composition of gut microbiota is influenced by both the animals' Sirt1 genotype and diet composition.—Caron, A. Z., He, X., Mottawea, W., Seifert, E. L., Jardine, K., Dewar‐Darch, D., Cron, G. O., Harper, M.‐E., Stintzi, A., McBurney, M. W. The SIRT1 deacetylase protects mice against the symptoms of metabolic syndrome. FASEB J. 28, 1306–1316 (2014). www.fasebj.org